Validity and Reliability of Turkish Version of the Functional Assessment of Cancer Therapy-Brain Questionnaire - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Background: Assessing the quality of life ( QOL) of patients with brain tumors is ever more important, given increasing survivorship and the higher likelihood of developing potential morbidities associated with new therapies. Objective: The aim of this study was to adapt the Functional Assessment of Cancer TherapyYBrain ( FACT-Br) Questionnaire for Turkish populations and test its validity and reliability. Methods: The questionnaire was first translated into Turkish and back-translated, adapting it to the Turkish culture. This Turkish version of the FACT-Br was administered to 500 patients. Confirmatory factor analysis was conducted to examine the scale's construct validity. Test-retest and Cronbach's alpha reliability coefficients were calculated to determine reliability of the total questionnaire and all subdimensions. Results: The questionnaire's factor structure demonstrated good fit, implying that it could be applied to the Turkish population. Interclass correlation coefficients were between 0.93 and 0.99. The 5 subscales demonstrated good internal consistency, with Cronbach's alpha ranging from.72 to.87. Overall, the reliability estimate for the total scale was 0.93. There was no difference between a 15-day test and retest coefficients for subscale and total scores, indicating stability. Conclusions: The Turkish version of the FACT-Br is a valid and reliable instrument that can be used to measure the QOL of patients with a brain tumor in Turkey. Implications for Practice: This assessment tool can be used in treatment evaluations and to evaluate other measures of QOL.
Keywords: Brain tumor; Quality of life; Questionnaires; Validity and reliability; QUALITY-OF-LIFE; TUMORS; GLIOMAS; ADULTS; SCALE